(untitled) (Research, Society and Development, 2021)
Objective: to describe the epidemiological profile of reported cases of schistosomiasis mansoni that occurred in Brazil in the period between 2013 and 2017. Methods: It is characterized as a descriptive and retrospective study, developed from data collected in SINAN. Data were obtained using Microsoft Excel® software. The research did not require evaluation by the Research Ethics Committee. Results: Incidence data in the study period accumulated a total of 28,781 cases. The Southeast region stood out with the highest number of cases, followed by the Northeast, North, Midwest and South regions. Minas Gerais, São Paulo and Bahia were the ones with the highest incidence of the illness, while the states of Acre, Roraima and Pará had the lowest rates. Among the variables evaluated, in association with parasitic disease, there was a greater predominance of males, adults, brown color and with low education. Final considerations: Brazil, despite having shown a decreasing trend in the number of cases in recent years, the number of cases is still considered high and, therefore, needs to establish better health policies aimed at the promotion, prevention and control of schistosomiasis.